Use of the Iraqi Song in the Orchestral Compositions of Hanz Moomer- (Foug Al-Nakhl) as a Model: فراس ياسين جاسم (Al-Academy, 2019)
The use of the Iraqi song in the symphony orchestra is one of the pioneering and important works, which carries with it an artistic value of aesthetic specificity in how to use the Iraqi singing heritage. The research aimed to identify the employment of the song (Foug Al-Nakhl) and its works within the Iraqi national symphony orchestra music by the author Hans Count Momer whose works still have a great influence on the authors of the Iraqi orchestra. The researcher presented a brief introduction to the Iraqi Symphony Orchestra, a brief introduction about the author, and the trends of world music towards heritage. He also talked about musical composition, research procedures and tools, and applying the tool to the selected sample (Foug Al-Nakhl). Then, the sample was analyzed and the results were reached as follows: the song was used in its traditional form in addition to the secondary tunes and was dealt with in the language of the orchestra and its expressions in the international orchestral composition